An Empirical Study On White-Collar Crime Announcement Effects On Shareholder Wealth : Evidence From Brazil - Law, Fung Yee (Universiti Malaysia Sarawak (UNIMAS), 2013)
Using a sample of 45 companies with 56 separate crimes in Brazil from 2001 to 2012, this study is mainly examines whether the white-collar crime announcement leads to abnormal return to the shareholders. The main objective in this study is to .. investigate and identify the announcement effect of white-collar crime towards the stock performance of the affected companies in Brazil. On the same time, it also to identify the stock market efficiency of the Brazil. This study adopted event study methodology and applied market model to determine the abnormal return for each securities. The AARs and CAARs for the overall sample of 56 announcements are insignificant at 5% level of significance. This implied that the white-collar crime does not have any impacts on the stock return on Brazil. So it can conclude that the strong efficiency market hypothesis supported on this study and these announcements bring little information value for investors